1993
DOI: 10.1159/000216881
|View full text |Cite
|
Sign up to set email alerts
|

First Experiences with the Heparin-lnduced Extracorporeal Low-Density Lipoprotein Precipitation in the Treatment of Critical Limb Ischaemia: A New Therapeutical Approach?

Abstract: The heparin-induced extracorporeal low-density lipoprotein (LDL) precipitation (HELP) system is based on the fact that besides lipoproteins even fibrinogen, which seems to be a very important factor in pathogenesis of peripheral arterial disease, is precipitated by high-dose heparin at acid pH values. The elimination of excess fibrinogen and lipoproteins, in particular LDL, leads to a markedly improved microcirculation. The restoration of the latter obviously enabled us to perform limb-saving surgical procedur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…2). It is possible that the improvement in rCBF can be related (as has been suggested for increased blood flow to the lower limbs in PAD [6,9,10]) to an effec tive reduction of fibrinogen as well as of lipo proteins, both influencing whole blood and plasma viscosity. In cases of hyperlipidemia, the RCTT, a measure related to the concen tration of lipoproteins [20], was improved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2). It is possible that the improvement in rCBF can be related (as has been suggested for increased blood flow to the lower limbs in PAD [6,9,10]) to an effec tive reduction of fibrinogen as well as of lipo proteins, both influencing whole blood and plasma viscosity. In cases of hyperlipidemia, the RCTT, a measure related to the concen tration of lipoproteins [20], was improved.…”
Section: Discussionmentioning
confidence: 99%
“…Recently it has been shown that HELP even in patients with PAD can lead to an improvement of clinical symptoms. This elimination of substances negatively in fluencing hemorheology was followed by an increase of blood flow and microcirculation in the lower limbs [6,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…2,8,9 Additionally, fibrinogen levels increase after an acute infarction, affecting the hemorrheologic pattern, such as whole blood and plasma viscosity as well as deformability and aggregability of red blood cells, causing a reduction in microcirculatory floW.2,6,8-10 A major goal in the management of infarctions and/or chronic occlusions should therefore include normalization of hyperfibrinogenemia.11,12 Several agents to improve hemorrheology and/or anticoagulant therapy are being studied. 2,8,9 Additionally, fibrinogen levels increase after an acute infarction, affecting the hemorrheologic pattern, such as whole blood and plasma viscosity as well as deformability and aggregability of red blood cells, causing a reduction in microcirculatory floW.2,6,8-10 A major goal in the management of infarctions and/or chronic occlusions should therefore include normalization of hyperfibrinogenemia.11,12 Several agents to improve hemorrheology and/or anticoagulant therapy are being studied.…”
Section: Introductionmentioning
confidence: 99%
“…6,9,[12][13][14][15][16][17][18][19] Hence, the HELP system is used to improve rheologic properties of blood during acute and/or chronic atherosclerotic events. 6,9,[12][13][14][15][16][17][18][19] Hence, the HELP system is used to improve rheologic properties of blood during acute and/or chronic atherosclerotic events.…”
Section: Introductionmentioning
confidence: 99%
“…Alternative applications LDL-apheresis alteration of vascular markers and immediate improvement of endothelial function [27•], nitric oxide levels, and microvascular flow has resulted in its use for other forms of acute and chronic vascular diseases resistant to standard medical therapy, such as peripheral vascular disease [28•], cerebral vascular disease [29], end-stage renal disease [30•], cardiac transplantation [31], dilated cardiomyopathy [32], ocular microcirculatory disturbances [33•], and sudden idiopathic hearing loss [34•]. Insurance coverage and LDL-apheresis therapy is almost universally covered by private health insurers, reimbursement for LDL-apheresis Medicare, and other government payers.…”
Section: Contraindications/complications/aesmentioning
confidence: 99%